2 A narrative review of key studies on the Heart Manual – looking back on 30 years of evidence on home-based cardiac rehabilitation. (21st November 2022) - Morris, Roseanne; Deighan, Carolyn; Cameron, Sharon; Taylor, Louise
Abstract : Background: The Heart Manual (HM) Programme is the UK's leading home-based self-managed cardiac rehabilitation programme (HBCRP) for individuals recovering from acute myocardial infarction and/or revascularisation. This year marks 30 years of HM implementation in the NHS and overseas. Aim: The aim of this study is to conduct a narrative review of the HM over the last 30 years, considering its outcomes as a HBCRP. Methods: Databases AHMED, Embase, APA PsychInfo, Ovid Medline were used to source studies where the HM outcomes were a key focus. Grey literature was searched by the HM department. Narrative synthesis was used to capture the qualitative element of extracted papers dated after the Heart Manual 2011 Systematic Review. Results: The search revealed 48 papers; 7 studies were already included in the 2011 systematic review (SR), with 4 new papers remaining and 1 grey-paper, others were duplicates. Of the studies and those included in SR, 9 reported on efficacy, 4 on programme adherence, and 2 on qualitative outcomes (1 digital-HM, 1 HM patient reported outcomes). Outcomes on efficacy and adherence were all positive. Qualitative findings (n=2) cited positive attitudes towards the HM from patient representatives, general user-friendliness and useful content. An audit on HM patient feedback reported high engagement with health behaviour change(s), positive gains from psychosocial support, and improved understanding and awareness of condition. A grey-paper on patient reported outcomes during COVID-19 reported improvements in managing other health conditions, including diabetes, blood pressure, and mental health, through using the HM. Patients also reported feeling reassured by the HM. Conclusion: The HM continues to be the most widely studied HBCRP, and has played a key role in demonstrating the effectiveness of HBCRP over the last 30 years. Recent surveys have shown reported benefits in managing other health conditions, accessibility, and providing psychological support.